Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Hasil Belajar Pada Mata Pelajaran Gambar Teknik Manufaktur Kelas XII Di SMK Semen Padang - Husnul Fiqri; Eko Indrawan; Refdinal Refdinal; Rahmat Azis Nabawi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to analyze the project-based learning model on learning outcomes in class XII Manufacturing Engineering Drawing subjects at SMK Semen Padang. The type of research used in this study is Quasy experimental using one experimental class and one control class. The study involved 20 experimental class students and 20 control class students. Data was collected with test questions in the form of pre-test and post-test to determine learning outcomes in aspects of Knowledge (cognitive), and assessment of student performance to determine learning outcomes in aspects of skills (psychomotor). Analyze the initial data to determine the average of the classes to be used for the determination of the experimental class and the control class. The final data analysis used is the T test. The results showed a significant influence on learning outcomes using a project-based learning model. The results of the T test on the Post-test results obtained a sig (2-tailed) value of 0.004 which is smaller than 0.05 with an average percentage of 71.8 in the Experiment class and 65.1 in the control class. For the T Test on student performance assessment, a sig (2-tailed) value of 0.027 is obtained which is smaller than 0.05. Both T-tests prove that project-based learning models can provide better learning outcomes.